Composition of the mitochondrial electron transport chain in Acanthamoeba castellanii: Structural and evolutionary insights - Gawryluk, Ryan M.R.; Chisholm, Kenneth A.; Pinto, Devanand M.; Gray, Michael W. (Biochimica et biophysica acta, 2012)
The mitochondrion, derived in evolution from an α-proteobacterial progenitor, plays a key metabolic role in eukaryotes. Mitochondria house the electron transport chain (ETC) that couples oxidation of organic substrates and electron transfer to proton pumping and synthesis of ATP. The ETC comprises several multiprotein enzyme complexes, all of which have counterparts in bacteria. However, mitochondrial ETC assemblies from animals, plants and fungi are generally more complex than their bacterial counterparts, with a number of ‘supernumerary’ subunits appearing early in eukaryotic evolution. Little is known, however, about the ETC of unicellular eukaryotes (protists), which are key to understanding the evolution of mitochondria and the ETC. We present an analysis of the ETC proteome from Acanthamoeba castellanii, an ecologically, medically and evolutionarily important member of Amoebozoa (sister to Opisthokonta). Data obtained from tandem mass spectrometric (MS/MS) analyses of purified mitochondria as well as ETC complexes isolated via blue native polyacrylamide gel electrophoresis are combined with the results of bioinformatic queries of sequence databases. Our bioinformatic analyses have identified most of the ETC subunits found in other eukaryotes, confirming and extending previous observations. The assignment of proteins as ETC subunits by MS/MS provides important insights into the primary structures of ETC proteins and makes possible, through the use of sensitive profile-based similarity searches, the identification of novel constituents of the ETC along with the annotation of highly divergent but phylogenetically conserved ETC subunits. ► We studied in detail the electron transport chain (ETC) of Acanthamoeba castellanii. ► This is the first broad proteomic analysis of the ETC for a member of Amoebozoa. ► We used profile-based bioinformatics to annotate divergent ETC subunits. ► We identified several novel subunits in the highly stable dimeric ATP synthase. ► Proteomic analysis confirmed novel structural features of several ETC proteins.